2016
DOI: 10.1111/nmo.12783
|View full text |Cite
|
Sign up to set email alerts
|

Electrical pharyngeal stimulation increases substance P level in saliva

Abstract: Electrical pharyngeal stimulation is able to induce pharyngeal SP release in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Thus, capsaicin and other pharmaceutical agents enhancing sensory input have been shown to improve swallowing safety in patients with dysphagia [ 19 , 20 , 21 ]. On the same note, pharyngeal electri cal stimulation is supposed to promote rehabilitation of neurogenic dysphagia – at least in part – by restoring peripheral sensory feedback [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, capsaicin and other pharmaceutical agents enhancing sensory input have been shown to improve swallowing safety in patients with dysphagia [ 19 , 20 , 21 ]. On the same note, pharyngeal electri cal stimulation is supposed to promote rehabilitation of neurogenic dysphagia – at least in part – by restoring peripheral sensory feedback [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, our group has shown that in healthy individuals, PES induces a temporary increase of SP concentration in saliva, but not in serum, whereas no effects were noticed in the sham condition [26]. In the present study, we moved this topic into the clinical context and tried to find out whether PES treatment in dysphagic stroke patients is also associated with changes in salivary SP concentrations, and, in particular, whether a potential increase in SP concentration is associated with treatment success.…”
Section: Introductionmentioning
confidence: 99%
“…The two main compensatory strategies used in the treatment of OD are modification of food textures for solids and liquids and the main rehabilitative interventions are behavioral treatments with swallow postures, maneuvers, and exercises . In contrast, there are new treatments that stimulate the recovery of the swallowing function, such as neurostimulation or chemical stimulation strategies, but in general they are still under investigation . No other active treatment has demonstrated utility in OD.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of SP have been found in dysphagic patients after stroke, in patients with delayed swallowing reflexes and a higher risk of pneumonia, in patients with aspiration pneumonia, and in patients using dopamine antagonists . In addition, it has been reported that some OD therapies, such as intrapharyngeal electrical stimulation, increase SP levels . The administration of capsaicin has been shown to be effective in reducing the onset time (latency) of the swallowing reflex in older patients with dysphagia, which is postulated to be due to the increase in SP .…”
Section: Introductionmentioning
confidence: 99%